Utility of specific amino acid ratios in screening for pyruvate dehydrogenase complex deficiencies and other mitochondrial disorders associated with congenital lactic acidosis and newborn screening prospects. Issue 1 (16th August 2020) - Bedoyan, Jirair K.; Hage, Rosemary; Shin, Ha Kyung; Linard, Sharon; Ferren, Edwin; Ducich, Nicole; Wilson, Kirkland; Lehman, April; Schillaci, Lori‐Anne; Manickam, Kandamurugu; Mori, Mari; Bartholomew, Dennis; et al.
Abstract: Pyruvate dehydrogenase complex deficiencies (PDCDs) and other mitochondrial disorders (MtDs) can (a) result in congenital lactic acidosis with elevations of blood alanine (Ala) and proline (Pro), (b) lead to decreased ATP production, and (c) result in high morbidity and mortality. With ~140, 000 live births annually in Ohio and ~1 in 9, 000 overall prevalence of MtDs, we estimate 2 to 3 newborns will have PDCD and 13 to 14 others likely will have another MtD annually. We compared the sensitivities of plasma amino acids (AA) Alanine (Ala), Alanine:Leucine (Ala:Leu), Alanine:Lysine and the combination of Ala:Leu and Proline:Leucine (Pro:Leu), in subjects with known primary‐specific PDCD due to PDHA1 and PDHB mutations vs controls. Furthermore, in collaboration with the Ohio newborn screening (NBS) laboratory, we determined Ala and Pro concentrations in dried blood spot (DBS) specimens using existing NBS analytic approaches and evaluated Ala:Leu and Pro:Leu ratios from DBS specimens of 123, 414 Ohio newborns in a 12‐month period. We used the combined Ala:Leu ≥4.0 and Pro:Leu ≥3.0 ratio criterion from both DBS and plasma specimens as a screening tool in our retrospective review of newborn data. The screening tool applied on DBS and/or plasma (or serum) AA specimens successfully identified three unrelated females with novel de novo PDHA1 mutations, one male with a novel de novo X‐linked HSD17B10 mutation, and a female with VARS2 mutations. This work lays the first step for piloting an NBS protocol in Ohio for identifying newborns at high risk for primary‐specific PDCD and other MtDs who might benefit from neonatal diagnosis and early institution of known therapy and/or potential novel therapies for such disorders.